Prediction of wetting phenomena of a microlayer of gas bubbles. (April 2019) - Ami, Takeyuki; Schulenberg, Thomas
Highlights: Physical modelling of the three-phase contact line including the electric double layer. Coulomb forces taken into account in the Navier-Stokes equations. Application of the method to an isothermal nano-bubble on a horizontal wall. Detailed dynamic simulation of contact angles. Prediction of the formation of microlayers. Abstract: With the aim to gain more understanding of the physics of nucleate boiling and its transition to film boiling, the dynamics of an isothermal bubble have been studied numerically on a nano-scale. Instead of postulating a contact angle, a microlayer or a precursor film during rewetting of a dry spot of a detaching bubble, the electrostatic forces of the electric double layer have been included in the Navier-Stokes equations to resolve the details of the three-phase contact line. Results show that the expected microlayer is formed only at elevated temperatures. The velocity profile inside this microlayer, its dynamic contact angle and its progression velocity could be determined for different temperatures.